Scholarly Portability in the Age of AI - Joseph W. Yockey (Washington University Journal of Law and Policy, 2026)
For decades, the “traditional academic works” exception harmonized university intellectual property policies with academic freedom, ensuring faculty retain ownership of their scholarly expression. However, the rise of generative artificial intelligence (AI) fundamentally unsettles this balance. Modern research now generates a novel class of artifacts—including prompt libraries, conversation logs, and fine-tuned large language models (LLMs)—that defy classification under the legacy binary of “personal scholarship” versus “institutional resource.” This Article addresses a critical, emerging governance gap: when a faculty member moves to a new institution, do these AI-era artifacts travel with them, or do they remain the property of the university? The Article demonstrates that existing doctrinal frameworks—including copyright, trade secret, contract law, and data governance—fail to provide stable default rules for AI-mediated scholarship. To remedy this failure, the Article proposes a normative framework of “scholarly portability” based on functional decoupling. It argues that universities should distinguish between three categories of artifacts and then assign tailored rights to each. First, scholarly expression and personal know-how (e.g., prompts and interaction histories) should remain faculty-owned and fully portable. Second, AI operational artifacts (e.g., fine-tuned models utilizing significant institutional compute) should be portable subject to a retained institutional “shop right”—by analogy to patent shop-right principles—structured as a non-exclusive, royalty-free license that preserves institutional continuity while permitting faculty mobility. Third, regulated data (e.g., FERPA- or HIPAA-protected inputs) must remain structurally non-portable, subject to rights of reconstruction via redactions, secure access, or synthetic data. Ultimately, this framework aligns institutional stewardship with the realities of AI-mediated inquiry, preventing the restraint of scholarly knowledge while respecting non-negotiable compliance obligations.
Keywords: #ScholarlyPortability; #AcademicFreedom; #AICopyright; #UniversityPolicy; #PromptLibraries